B-cell response in solid organ transplantation - Yi, Stephanie G.; Gaber, Ahmed Osama; Chen, Wenhao (Frontiers in Immunology, 2022)
The transcriptional regulation of B-cell response to antigen stimulation is complex and involves an intricate network of dynamic signals from cytokines and transcription factors propagated from T-cell interaction. Long-term alloimmunity, in the setting of organ transplantation, is dependent on this B-cell response, which does not appear to be halted by current immunosuppressive regimens which are targeted at T cells. There is emerging evidence that shows that B cells have a diverse response to solid organ transplantation that extends beyond plasma cell antibody production. In this review, we discuss the mechanistic pathways of B-cell activation and differentiation as they relate to the transcriptional regulation of germinal center B cells, plasma cells, and memory B cells in the setting of solid organ transplantation.